Two interpretations of Gilbert’s plural-subject account - Giulia Lasagni (Rivista di Estetica, 2022)
The notion of collective action is one of the most discussed topics in contemporary social ontology, which offers different explanations of how two or more individuals can act together in the pursuit of a common goal. Many believe that collective intentionality is at the basis of actions of this kind, whereas others deny that collective actions have a distinctive nature or involve different faculties than those required by individual actions. The article aims to outline the most influential approaches to collective agency and discuss the disputed case of Margaret Gilbert’s theory, which is subject to conflicting interpretations. I start from asking the question: what is it that makes a group of people act together intentionally? First, I will outline three approaches offered in social ontology, i.e., content, mode, and subject account. Then, I will focus on Gilbert’s view, allegedly a proponent of the (plural) subject account. The main purpose of these pages is to show that Gilbert’s approach should rather be classified as a mode account and that the interpretation attributing to her a subject account is, if not to be discarded, at least to be regarded as uncertain. While some scholars have questioned the theory of plural subjects as presented in Gilbert’s early essays, this article makes the point by considering Gilbert’s latest publications.